PENGGUNAAN PENJULUKAN DI KALANGAN REMAJA - Atik Khoiroti; Rahutami Rahutami; Suryantoro Suryantoro (Kantor Bahasa Provinsi Maluku Utara, 2021)
This study aims to describe the use of the form and referent nicknames of adolescents. The nickname indicated the freedom of language that comes from adolescents identity. The method of this study is descriptive qualitative method of nicknames used by participants as research data. The participants are teenage students. Data collected using questionnaire technique and analysis technique used pragmatic matching technique to analyze the form of nicknames and the referential matching technique to analyze the nickname referent. The results showed that the various forms of nicknames included the use of likenesses, mention of distinctive traits, events, names of parents, occupations, likes and negations. Relative nicknames use harsh vocabulary and referents are negative / bad. The use of nicknames among adolescents as a form of expression of feelings (intimacy) adolescents towards others. This familiarity is manifested in the use of harsh and negative nicknames, but there is no problem or offense for the subject.